Pengaruh ekstrak propolis (trigona sp.) Yang dilarutkan dalam saliva buatan terhadap pertumbuhan candida albicans - Dewi Priandini; Nadya Callista Ludy (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Xerostomia often occurs in the elderly and can be overcome by administering artificial saliva. Xerostomia is closely related to the incidence of oral candidiasis. Candida albicans is the main fungal species that causes oral candidiasis. To minimize the risk of oral candidiasis in patients with xerostomia, it is necessary to add antifungal agents to artificial saliva. Propolis extract (Trigona Sp.) contains antifungal compounds which are expected to inhibit the growth of Candida albicans. Objective: To determine the effect of adding propolis extract with artificial saliva on the growth of Candida albicans. Method: In vitro laboratory experiment with a post test only control group design. The test solutions used were propolis extract (Trigona Sp.) 15.625 mg/ml, 31.25 mg/ml, 62.5 mg/ml, 125 mg/ml and 250 mg/ml, nystatin as a positive control, and artificial saliva as a negative control. Antifungal test was carried out by disc diffusion method. Results: Propolis extract (Trigona Sp.) added with artificial saliva showed an inhibition zone start from concentration of 15.625mg/ml until 250mg/ml. The highest inhibition zone is at concentration of 62.5mg/ml. Conclusion: Propolis extract (Trigona Sp.) added with artificial saliva can inhibit the growth of Candida albicans.